2021
DOI: 10.3390/cells10030628
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Aging May Be Associated with COVID-19 Pathophysiology in the Elderly

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the global pandemic of coronavirus disease 2019 (COVID-19) and particularly exhibits severe symptoms and mortality in elderly individuals. Mounting evidence shows that the characteristics of the age-related clinical severity of COVID-19 are attributed to insufficient antiviral immune function and excessive self-damaging immune reaction, involving T cell immunity and associated with pre-existing basal inflammation in the elderly. Age-related ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 136 publications
(129 reference statements)
0
25
1
Order By: Relevance
“…Thus, aging of the immune system itself would both directly and indirectly affect the course of COVID-19. The first reason would be the decreased ability of the aging IS to recognize the new virus, SARS-CoV-2, due to greatly reduced output of new naïve T cells from involuted thymus [ 113 , 114 ]. Next, the immunosenescence - remodeled IS of the elderly individuals would reduce its ability to build effective response to the virus, which exists in significantly higher load in the elderly, especially burdened with advanced immunosenescence [ 41 , 115 ].…”
Section: Covid-19 – Why It Is More Severe and Deadly In Elderly?mentioning
confidence: 99%
“…Thus, aging of the immune system itself would both directly and indirectly affect the course of COVID-19. The first reason would be the decreased ability of the aging IS to recognize the new virus, SARS-CoV-2, due to greatly reduced output of new naïve T cells from involuted thymus [ 113 , 114 ]. Next, the immunosenescence - remodeled IS of the elderly individuals would reduce its ability to build effective response to the virus, which exists in significantly higher load in the elderly, especially burdened with advanced immunosenescence [ 41 , 115 ].…”
Section: Covid-19 – Why It Is More Severe and Deadly In Elderly?mentioning
confidence: 99%
“…Remarkably, it has been described that thymic function failure predicts all-cause mortality in healthy elderly people (Ferrando-Martínez et al, 2013) and has a relevant role in viral infections such as HIV-1 infection (Delgado et al, 2002; Douek et al, 1998; Ferrando-Martinez et al, 2017). Moreover, it has been suggested that thymic aging might have an important implication in COVID-19 disease severity (Kellogg and Equils, 2021; Wang et al, 2021). Importantly, we discovered that the thymic dysfunction, along with the memory inflation and a higher homeostatic T cell proliferation and activation found in old people, were correlated to a lower response to SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were also shown in SARS-CoV-1 ( 102 ), MERS ( 103 ),and experimental models of SARS-CoV-2 infection ( 104 ). It is proposed that immunosenescence and inflammaging are high-risk factors for severe COVID-19 in the elderly, suggesting that the age-related clinical severity of COVID-19 is due to impaired antiviral immune function and excessive self-damaging immune reactions in the elderly ( 101 , 105 ). Others also posited that the advanced age population is highly prone to viral infection because of a lower functional capacity of phagocytes to eliminate pathogens and activate the adaptive immune response ( 106 , 107 ).…”
Section: Thymic Injury: Factors and Agentsmentioning
confidence: 99%